An Analysis of the Main Character’s Personality Development in Harry Potter and the Order of the Phoenix: A Descriptive Analysis on J.K Rowling’s Novel - Faraditha, Uzla Aulia; Rezeki, Yanti Sri; Wardah, Wardah; Rosnija, Eni; Surmiyati, Surmiyati (Tamaddun Life, 2022)
This study aims to describe the personality development of a character in a novel. The object of this research is Harry Potter from the novel written by J.K. Rowling's, ‘Harry Potter and the Order of the Phoenix’. This study uses a descriptive method and data is collected by reading and taking important things from the novel that can be used as research material. Harry Potter's characteristic is described as brave, caring, curious, bad-tempered, insolent, and stubborn through personal description, speech, reactions, and character as seen by others. The results show that the character's personality development occurs slowly during the story. Character’s personality development can be observed by comparing the character's personality at the beginning of the story to the end. It can be observed in each chapter through the character's ways of talking, character's behaviour, character's emotions, and character's actions. From this research, it can be concluded that Harry experiences a series of external and internal events that affects his feelings and emotions, which could also affect the development of his personality.